Apatinib Plus Temozolomide: An Effective Salvage Treatment for Recurrent Glioblastoma - Ge, Jingjing; Li, Cheng; Xue, Fengjun; Qi, Shaopei; Gao, Zhimeng; Yu, Chunjiang; Zhang, Junping (Frontiers in Oncology, 2021)
Background: Treatment for recurrent glioblastoma is poor and there is a need for better therapies. Here we retrospectively assessed the efficacy and toxicity of temozolomide plus apatinib, an oral small-molecule tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor 2 in recurrent glioblastoma. Materials and methods: A retrospective analysis of patients with recurrent glioblastoma who underwent apatinib plus temozolomide treatment was performed. Apatinib was given at 500mg once daily. Temozolomide was administered at 200 mg/m2/d on days 1-5 or 50 mg/m2/d continuous daily according to whether they had experienced temozolomide maintenance treatment before. The main clinical data collected included tumor characteristics, status of MGMT promoter and IDH mutation, number of relapse, response, survival, adverse reactions and salvage therapies. Results: From April 2016 to August 2019, thirty-one patients were identified. The objective response rate was 26.3%, and the disease control rate was 84.2%. The progression-free survival (PFS) at 6 months and overall survival (OS) at 12 months were 44.6% and 30.2%. The median PFS and OS were 4.9 and 8.2 months, respectively. Two patients achieved long PFS of 30.9 and 38.7+ months. The median survival time after progression of the patients with or without salvage bevacizumab was 5.1 versus 1.2 months. The most common grade 3 or 4 toxicities were hypertension (5.8%), decreased appetite (5.8%) and thrombocytopenia (4.3%), most of which were resolved after symptomatic treatment or dose reduction. Conclusion: Apatinib plus temozolomide is an effective salvage regimen with manageable toxicities for recurrent glioblastoma and could not reduce the sensitivity to bevacizumab.